Three new Brazilian species of the sharpshooter genus Amblyscarta Stål, 1869 and redescription of A. unifasciata (Fabricius, 1803) comb. nov. (Insecta: Hemiptera: Cicadellidae: Cicadellini) - Mejdalani, Gabriel; Domahovski, Alexandre C.; Cavichioli, Rodney R. (Zootaxa, 2019)
Three new Brazilian species of the sharpshooter genus Amblyscarta Stål, 1869 are described and illustrated: A. elianeae sp. nov. (states of Paraná and Minas Gerais), A. souzalopesi sp. nov. (State of Rio de Janeiro), and A. pinna sp. nov. (State of Mato Grosso). The first two species are from the Atlantic Forest, whereas the third is from the Amazon Forest. Cicada unifasciata Fabricius, 1803 is redescribed and transferred to Amblyscarta based on specimens from Guyana and northern Brazil (Amazon Forest). This Fabrician species is the type of the monobasic genus Strictogonia Melichar, 1926, which is thus considered a junior synonym of Amblyscarta. A diagnosis of Amblyscarta is added, as well as brief notes on the phenology of A. elianeae. This paper provides the first detailed descriptions and illustrations of the female terminalia of Amblyscarta species.